Pola Distribusi Hujan Jam-Jaman (Studi Kasus Stasiun Hujan Kecamatan Senapelan) - Saragi, Setiadi; Handayani, Yohanna Lilis; Hendri, Andy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Rainfall distribution pattern in Senapelan (Pekanbaru) can not be known certainly Rainfall distribution can be preditced by hourly rainfall distribution. The pattern of hourly rainfall distribution can be calculated with empirical method or observation method. Empirical method process the daily rainfall with ABM (Alternating Block Methods), Tadashi Tanimoto rainfall distribution and Mononobe Modifed method. Observation method using rainfall hourly data. Based on the analysis,the highest incidence of rain in Senapelan the duration of 3 hours. Based on the comparison chart obtained form rain duration 3 hours and 7 hours approaching dsitribusi pattern ABM (Alternating Block Methods), rainfall duration of 4 hours and 5 hours approaching Mononobe Modified distribution patterns. The comparison is based on the duration of the show that the duration of the 3, 4, 5, 6, 7, and 8 approach the distribution pattern of the ABM method (Alternating Block Methods).Keyword: Rainfall distribution, Alternating Block Methods, Modified Mononobe Methods, Tadashi Tanimoto